Analysis the Effect of Green Brand Knowledge and Consumer Perceptions Toward Purchase Intention on Green Products in the Pandemic Era - Dadan Abdul Aziz Mubarok; Rama Chandra Jaya; Palupi Permata Rahmi (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
The back to nature trend is in great demand by various groups in Indonesia, especially in choosing products, especially tumblers. The purpose of this study is to determine and analyze purchase intention on green products, especially tumbler products in the pandemic era. This research was conducted in the city of Bandung. The research method uses quantitative methods with descriptive and verification analysis. The research population is the population of the city of Bandung. The number of research samples is 100 respondents, with the sampling method using simple random sampling. Data analysis using path analysis. The results of the study explain that green brand knowledge affects consumer perceptions. Consumer perceptions has effect on purchase intention on green products in the pandemic era. However, based on research shows that Green Brand Knowledge has direct and indirect effect on Purchase Intention. the direct influence value is 0.104 and the indirect effect is 0.439. This explains that indirectly Green Brand Knowledge through Consumer Perception has a significant influence on Purchase Intention